Travel password: A secure and memorable password scheme - Nattawut Phetmak (2018)
There is a trade-off between password security and usability; longer password provides higher security but can reduce usability, as it is harder to remember. To address this challenge, this paper proposed a novel password scheme, called "Travel Password", which is memorable and also secure. The proposed scheme is designed to aid human memory by using mnemonic device, e.g., pictures and symbols, and story telling. Mnemonic device aids memory because human can remember pictures better than text. Story telling, on the other hand, allows users to make connection between each part of the password. The experiment with eighty users shows that the proposed scheme allows users to have better password recall. Compared with traditional textual password which has about 0.8 recall rate for strong passwords, users with the proposed scheme can achieve 1.0 recall rate. Moreover, the proposed scheme is more memorable than the traditional textual one. 90% of users can promptly remember strong passwords in the proposed scheme, compared with 58% of the textual one. © 2014 Springer International Publishing Switzerland.